Language therapy and functional improvement in aphasia - B, Hemalatha (Journal of All India Institute of Speech and Hearing)
The major aim of the study was to check the efficacy of language therapy for aphasics based on the Linguistic Profile Therapy (Karanth, 1986) and to identify the reflection of such therapy in a patients daily communication profile (Sarno, 1965).